Vehicle communications: Sensitive node election SNE algorithm achieves optimized QoS - Ayoob, Ayoob A.; Mohd Faizal, Ab Razak; Khalil, Ghaith; Aksoy, Muammer (MDPI, 2026)
Vehicle networking is a new paradigm in wireless technology that facilitates communication between vehicles in close proximity and in-vehicle internet access. This technology paves the way for a variety of safety, convenience and entertainment applications, including safety message exchange, real-time traffic information sharing and public internet access. The overall goal of vehicular networks is to create an efficient, safe and convenient environment for vehicles on the road. This paper presents a Sensitive Node Election (SNE) algo- rithm adapted to routing protocols in certain opportunistic network environments. The algorithm focuses on selecting the best agent for communication using an innovative approach for message forwarding. Quality of Service (QoS) metrics targeted for optimization include network end-to-end Throughput packets delivery with the aim of improving overall performance of network. Our algorithm includes a stochastic rebroadcasting scheme that takes into account parameters such as vehicle density, distance between vehicles and transmission distance, and adapts to various network conditions. Furthermore, the SNE algorithm uses a metric based on transmission distance and can dynamically adapt to application requirements, such as prioritizing it provides high throughput and minimized delay. Results demonstrate the effectiveness of this approach in improving QoS in various VANET simulations.